Imagen, escritura y diferencia cultural en la conquista de América - Martínez Toledo, Yanet (2013)
The construction of the Other in the process of conquest of America in the sixteenth century, despite its multidimensionality could be summed up in one constant: the ranking of Spanish “Self”, through the establishment of cultural difference. The interpretation that makes the conquerors of the indigenous culture is not only biased and culturally situated. With its claim to universality is trying to show the superiority of the world regarding indigenous civilization. The concepts of image and writing, will be central in building the other, mediated by the difference.